Bangkinang Trade Center Dengan Pendekatan Arsitektur Kontemporer - Winny Zuliati; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bangkinang currently does not have any appropriate facilities yet to accommodate and manage increasing trade activities. The growth of modern shopping centers as commercial areas reflects a form of trade and entertainment activities in a city that includes trade and service. Bangkinang has potency and competitiveness, so that economic development is needed for advancing the regional economic sector. Bangkinang Trade Center is a trading business center that can accommodate a variation of activities ranging from recreation, culinary, and buying and selling various kinds of goods to handicraft products. Trade Center is designed with a Contemporary Architecture approach aimed at making this facility grow rapidly and progressively, so it can make people interested to visit. The results of this design with the Stability concept are interpreted as stable and balanced. This concept is adapted to the guidelines of the theme of contemporary architecture and has a close relationship with the Trade Center. The main facilities that available at this Trade Center are convention rooms, exhibition halls, and retailers to accommodate traders. There are also supporting facilities such as restaurants and food court.Key word: Contemporary Architecture, Stability, Trade Center